Hereditary alpha tryptasemia: elevated tryptase, female sex, thyroid disorders, and anaphylaxis - Puxkandl, Viktoria; Aigner, Stefan; Hoetzenecker, Wolfram; Altrichter, Sabine (Frontiers in Allergy, 2024)
IntroductionThe clinical significance of elevated baseline serum tryptase (BST) in the absence of mast cell disorders or allergic reactions has long been unclear. Recently, a genetic variation of the TPSAB1 gene, which among others encodes for alpha tryptase, has been reported and named hereditary alpha tryptasemia (HaT). HaT has been linked to various manifestations, including severe allergic reactions. However, clinical studies are limited. In this study, we aimed to determine HaT prevalence and characterize its clinical manifestations in patients at a specialized allergy center.MethodsFrom January 2022 to December 2023, patients with elevated BST at least once were screened for HaT at the outpatient clinic. A control group included patients with a history of anaphylaxis undergoing specific Hymenoptera immunotherapy. TPSAB1 copy numbers, BST levels, and clinical parameters were assessed and analyzed.ResultsOf 47 patients with elevated BST (≥11.4 µg/L), 93% showed increased TPSAB1 copy numbers. Individuals diagnosed with HaT displayed a BST range between 12.3 and 28.4 µg/L, with 84.1% associated with TPSAB1 duplication and 15.9% with triplication. HaT predominated in women (86.4%) and was associated with thyroid disease (27.3%). Over half had a history of anaphylaxis (54.5%), which was mainly low-grade.DiscussionIn patients with elevated BST but no mastocytosis, the most likely cause of elevated BST was an increase in the copy number of the TPSAB1 gene. A heightened risk of anaphylaxis should be considered. Further research is needed to explore the predominance of women and the emerging link with thyroid disease.